Religion and COVID-19 Vaccination: The Use of Religious Language in Vaccination Socialization in New Media - mualimin mualimin (UIN Sulthan Thaha Saifuddin Jambi, 2022)
This study aims to explore using religious language to socialize the COVID-19 vaccination in new media. This study is qualitative research. The source of data in this study is the official online platform of the Komite Penanganan COVID-19 Republic of Indonesia's, namely websites and social media. The data collected is related to the use of religious language in socializing the COVID-19 vaccination. Data collection is carried out through observation of the official online platform. The data obtained were then analyzed by means of an interactive qualitative analysis model of Miles and Huberman: data collection, data display, data reduction, and drawing conclusions. There are three findings in this study. First, religious terms and language used in the socialization of COVID-19 vaccination have a pattern based on the dynamics of socio-cultural reality and vaccination achievements. Second, the terms and religious language used to relate to the legitimacy of the permissibility and halalness of vaccines. This tendency aims to convince the public of the vaccination program. Third, religious figures, institutions, and facilities are used as tools to legitimize socialization messages. Departing from these findings, it can be concluded that religion is not only related to the dimension of spirituality but also consumed and commodified with a specific purpose. In the context of this study, the consumption and commodification of religion were carried out by the Komite Penanganan COVID-19 in the socialization of vaccination using religious terms, narratives, and language as legitimacy tools to convince the public about the importance of vaccination.